2010
DOI: 10.1111/j.1399-3062.2009.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Human metapneumovirus infection in hematopoietic stem cell transplant recipients

Abstract: hMPV has been reported as a respiratory pathogen in HSCT patients. We suggest that hMPV infection should be routinely investigated in this population, mainly in children, to prevent nosocomial transmission during transplant proceedings and to avoid the risk of progressing to complications due to LRTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 32 publications
2
40
0
1
Order By: Relevance
“…One prospective study found that 40% of HMPV infections in 22 adults with hematologic malignancies progressed from upper respiratory infection to pneumonia, with case-fatality close to 14% [9]. Other studies in HCT recipients have shown pneumonia rates of 28% and mortality rates of 0-4% [19-21*]. Among 163 HCT recipients who underwent BAL for the work-up of pulmonary infiltrates, HMPV was detected in BAL samples from 5 of 163 (3%) patients; 4 of the 5 died with acute respiratory failure highlighting the potential severity of HMPV pneumonia [52].…”
Section: Newly Discovered Respiratory Virusesmentioning
confidence: 99%
“…One prospective study found that 40% of HMPV infections in 22 adults with hematologic malignancies progressed from upper respiratory infection to pneumonia, with case-fatality close to 14% [9]. Other studies in HCT recipients have shown pneumonia rates of 28% and mortality rates of 0-4% [19-21*]. Among 163 HCT recipients who underwent BAL for the work-up of pulmonary infiltrates, HMPV was detected in BAL samples from 5 of 163 (3%) patients; 4 of the 5 died with acute respiratory failure highlighting the potential severity of HMPV pneumonia [52].…”
Section: Newly Discovered Respiratory Virusesmentioning
confidence: 99%
“…10 A more recent report, however, described a mild course of illness and complete recovery from hMPV infection in HSCT recipients including children. 11 We conducted a retrospective study to describe the clinical features and severity of hMPV in pediatric oncology patients at The Hospital for Sick Children, Toronto, Canada.…”
mentioning
confidence: 99%
“…29 Other study data show that RBV does not reduce mortality in immunocompromised patients and is not effective against the virus. 30 Although case 1 in our series is an example of successful treatment against HMPV using oral RBV, this finding does not establish a beneficial effect of RBV against HMPV infection.…”
Section: Discussionmentioning
confidence: 71%